Scapulothoracic Anatomy and Snapping Scapula Syndrome. (28th November 2013) - Frank, Rachel M.; Ramirez, Jose; Chalmers, Peter N.; McCormick, Frank M.; Romeo, Anthony A.
Abstract : The scapulothoracic articulation is a sliding junction between the deep aspect of the scapula and thoracic rib cage at the levels of ribs 2 through 7. Motion at this articulation is dynamically stabilized by a variety of muscular attachments, allowing for controlled positioning of the glenoid to assist in glenohumeral joint function. A thorough understanding of the complex anatomic relationships, including the various muscles, and bursa, is critical to the evaluation of patients presenting with scapulothoracic disorders. The snapping scapula syndrome is caused by either osseous lesions or scapulothoracic bursitis and can be difficult to recognize and treat. The purpose of this review is to discuss the anatomy of the scapulothoracic articulation with an emphasis on the pathology associated with snapping scapula syndrome.